1972
DOI: 10.1111/j.1365-2141.1972.tb08795.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulopoiesis in Chronic Granulocytic Leukaemia*

Abstract: Summary: The disappearance from the blood was studied of (1) leucocytes of patients with chronic granulocytic leukaemia labelled in vitro with DF32P and irradiated with 1500 rad, and (2) in vitro labelled normal marrow leucocytes. These studies made it possible to estimate the intravascular phase of the lifespan of mature leukaemic neutrophils and to compute the granulocyte turnover rate when immature leucocytes (myelocytes) were present in the blood. The studies support the hypothesis that immaturity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…During the chronic phase of CML, an expansion of the leukemic cells occurs which leads to an approximately 5 ± 10-fold increase in total hematopoietic cell mass (Clarkson and Strife, 1993). While these cells do not have an increased proliferative rate, they do undergo extra cell divisions and have longer survival times than normal myeloid progenitors (Athens et al, 1965;Chervenick and Boggs, 1968;Clarkson and Strife, 1993;Galbraith and Abu-Zahra, 1972;Goto et al, 1982;Ogawa et al, 1970;Scott et al, 1971;Strife and Clarkson, 1988;Stryokmans et al, 1977). Mitogenic signals from Bcr-Abl may serve to inhibit cell cycle exit that would normally occur during the dierentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…During the chronic phase of CML, an expansion of the leukemic cells occurs which leads to an approximately 5 ± 10-fold increase in total hematopoietic cell mass (Clarkson and Strife, 1993). While these cells do not have an increased proliferative rate, they do undergo extra cell divisions and have longer survival times than normal myeloid progenitors (Athens et al, 1965;Chervenick and Boggs, 1968;Clarkson and Strife, 1993;Galbraith and Abu-Zahra, 1972;Goto et al, 1982;Ogawa et al, 1970;Scott et al, 1971;Strife and Clarkson, 1988;Stryokmans et al, 1977). Mitogenic signals from Bcr-Abl may serve to inhibit cell cycle exit that would normally occur during the dierentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…324,422,424,425 The rates of cell production are similar in the marrow and spleen, and in patients with massive splenic involvement, the majority of circulating immature granulocytes may originate in the spleen. 324,430 Leukocyte kinetic studies [431][432][433][434][435] have shown that the size of the total blood granulocyte pool in CML patients may be 10-100 times greater than normal; both the circulating granulocyte pool (CGP) and marginated granulocyte pool are grossly expanded.…”
Section: Cell Cycle and Other Kinetic Parametersmentioning
confidence: 99%
“…Chronic myeloid leukaemia (CML) is a clonal, pluoripotent stem cell disorder characterized by the occurrence of Philadelphia chromosome (Ph 1 ) and presence of a large number of mature and immature myeloid cells in the peripheral blood [7]. Earlier work from our laboratory has shown that PMNL from CML patients were defective in actin dependent functions such as chemotaxis, degranulation, endocytosis, etc.…”
Section: Introductionmentioning
confidence: 99%